Subseasonal Analysis of Precipitation Variability in the Blue Nile River Basin - Berhane, Fisseha; Zaitchik, Benjamin; Dezfuli, Amin (Journal of climate, 2014)
The Ethiopian portion of the Blue Nile River basin is subject to significant interannual variability in precipitation. As this variability has implications for local food security and transboundary water resources, numerous studies have been directed at improved understanding and, potentially, predictability of the Blue Nile rainy season (June–September) precipitation. Taken collectively, these studies present a wide range of large-scale drivers associated with precipitation variability in the Blue Nile: El Niño–Southern Oscillation (ENSO), the Indian summer monsoon, sea level pressure (SLP) anomalies over the Arabian Peninsula and Gulf of Guinea, the quasi-biennial oscillation (QBO), and dynamics of the tropical easterly jet (TEJ) and African easterly jet (AEJ) have all been emphasized to varying degrees. This study aims to reconcile these diverse analyses by evaluating teleconnection patterns and potential mechanisms of association on the subseasonal scale. It is found that associations with the TEJ, Pacific modes of variability, and the Indian monsoon are strongest in the late rainy season. Mid–rainy season precipitation (July and August) shows mixed associations with Pacific/Indian Ocean variability and Atlantic Ocean indices, along with connections to regional pressure patterns and the AEJ. June precipitation is negatively correlated with SLP over the equatorial Atlantic and upper-tropospheric geopotential height. June and July precipitation show little significant correlation with the sea surface temperature over the equatorial Pacific Ocean. The observed intraseasonal evolution of teleconnections across the rainy season indicates that subseasonal analysis is required to advance understanding and prediction of Blue Nile precipitation variability.